2009
DOI: 10.1128/jb.00818-09
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Biochemical Analysis of the Interaction ofBacillus subtilisCodY with Branched-Chain Amino Acids

Abstract: Bacillus subtilis CodY protein is a DNA-binding global transcriptional regulator that responds to branchedchain amino acids (isoleucine, leucine, and valine) and GTP. Crystal structure studies have shown that the N-terminal region of the protein includes a GAF domain that contains a hydrophobic pocket within which isoleucine and valine bind. This region is well conserved in CodY homologs. Site-directed mutagenesis was employed to understand the roles of some of the residues in the GAF domain and hydrophobic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 52 publications
2
49
0
Order By: Relevance
“…These results demonstrated that CodY DNA-binding activity was enhanced 5-fold in the presence of isoleucine. Although this level of CodY DNA-binding enhancement is similar to that found in previously published reports (44,46), it is rather low compared to that seen for other DNA-binding proteins. For example, the DNA-binding activities of the TrpR and PurR repressors are enhanced 200-fold by their corepressors (9,51).…”
Section: Resultssupporting
confidence: 47%
“…These results demonstrated that CodY DNA-binding activity was enhanced 5-fold in the presence of isoleucine. Although this level of CodY DNA-binding enhancement is similar to that found in previously published reports (44,46), it is rather low compared to that seen for other DNA-binding proteins. For example, the DNA-binding activities of the TrpR and PurR repressors are enhanced 200-fold by their corepressors (9,51).…”
Section: Resultssupporting
confidence: 47%
“…Previous results indicated that CodY binds to different target sites with varying affinity (29,37). Furthermore, significant variation has been observed in the extent to which mutations in CodY that affect its DNA-binding activity alter the regulation of a limited number of its direct targets (17,37,38). These findings suggest that not all genes regulated by CodY respond equally to a given extent of nutritional limitation (27,37).…”
Section: Rna-seq Reveals a Graded Transcriptional Response Mediated Bymentioning
confidence: 67%
“…To verify that the variable activities of the mutant set used for the experiments reported here was related to the presence of ILV, we measured transcript abundance for bcaP (a direct CodY target) in strains producing WT CodY and the mutant forms F71Y, R61K, and R61H (ref. 38 and this study), all of which have single amino acid substitutions in the ILV-binding pocket (Fig. S1).…”
Section: Rna-seq Reveals a Graded Transcriptional Response Mediated Bymentioning
confidence: 99%
See 1 more Smart Citation
“…Protein CcpA is expressed by reaction r 6 and degraded by reaction r 6 . Transcription at the ilv-leu promoter is well known to be inhibited by CodY through a binding of this latter on the promoter [7,9,14,16,17]. To model this action of CodY on the promoter PIlv鈭扡eu, we introduce the reaction r 4 which activates the binding side BS CodY of CodY at the promoter, which in turn slows down reaction r 5 and thus reduces the promoter's activity.…”
Section: Example: Regulation Of Metabolism Of B Subtilismentioning
confidence: 99%